Rancang Bangun Jemuran Otomatis Menggunakan Mikrokontroller WEMOS - Adetya Windiarto Makhmud; Tutus Praningki; Ira Luvi Indah (CAHAYAtech, 2020)
Drying clothes is one of the daily activities of people who use solar energy. With these conditions, people are very dependent on weather conditions that are sometimes erratic. One of the right ways is by utilizing technology, namely using an automatic clothesline using a Wemos D1Mini microcontroller, equipped with an LDR sensor that will read light intensity and the DHT11 sensor will read humidity and temperature around the environment. This tool is also based on the Internet of Things which can be accessed from anywhere as long as it is connected to the internet. Keyword: Microcontroller, LDR sensor, DHT11 sensor, Internet of Things.